Neutrino decay and neutrinoless double beta decay in a 3-3-1 model - Dias, Alex G.; Doff, A. [UNESP]; De, C. A.; Rodrigues Da Silva, P. S. (American Physical Society (APS), 2005)
In this work we show that the implementation of spontaneous breaking of the lepton number in the 3-3-1 model with right-handed neutrinos gives rise to fast neutrino decay with Majoron emission and generates a bunch of new contributions to the neutrinoless double beta decay. © 2005 The American Physical Society.